1993
DOI: 10.1128/aac.37.11.2337
|View full text |Cite
|
Sign up to set email alerts
|

Development of halofantrine resistance and determination of cross-resistance patterns in Plasmodium falciparum

Abstract: Intermittent exposure to halofantrine (HF) of both chloroquine-susceptible (T9.96) and chloroquine-resistant (K1) isolates of Plasmodium falciparum in vitro resulted in a rapid reduction in susceptibility to HF. After 6 months, the 50%o inhibitory concentration (IC..) (14,19,22,23) or the exposure of cultures to mutagenic agents followed by drug pressure to select for resistant mutants (1,16,17). However, the relevance of resistance mechanisms developed as a result of mutagenesis to resistance mechanisms de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…32 However, other studies showed that the acquisition of reduced halofantrine susceptibility was accompanied by similar shifts in sensitivity to quinine, mefloquine, and other antimalarial agents containing the methanolic function, but increased susceptibility to chloroquine. This suggests that the methanolic functional group is essential for activity or is of importance in the resistance mechanism, 33 resistance to halofantrine, quinine, and mefloquine is related to reduced drug accumulation within the parasite, and that this can be achieved without overexpression of Pgh 1. 34 Pyronaridine contains a methanolic functional group.…”
Section: Resultsmentioning
confidence: 99%
“…32 However, other studies showed that the acquisition of reduced halofantrine susceptibility was accompanied by similar shifts in sensitivity to quinine, mefloquine, and other antimalarial agents containing the methanolic function, but increased susceptibility to chloroquine. This suggests that the methanolic functional group is essential for activity or is of importance in the resistance mechanism, 33 resistance to halofantrine, quinine, and mefloquine is related to reduced drug accumulation within the parasite, and that this can be achieved without overexpression of Pgh 1. 34 Pyronaridine contains a methanolic functional group.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known for some time that CQR culture‐adapted field isolates are often hypersensitive to the anti‐influenza drug amantadine (Evans and Havlik, 1993) and to the phenanthrene methanol, halofantrine (Nateghpour et al ., 1993). Using a stepwise selection protocol, CQR lines were selected for increasing levels of resistance to either amantadine or halofantrine.…”
Section: The ‘Charged Drug Leak’ Hypothesismentioning
confidence: 99%
“…Sequencing of the K1HF pfcrt cDNA revealed three polymorphisms: a codon 152 threonine to alanine substitution (T152A), S163R, and a codon 275 proline to leucine substitution (P275L). Thus the same mutation (S163R) was selected, accompanied by the same phenotypic change, in independent experiments that used two structurally unrelated drugs, both of which display inverse crossresistance with CQ (Oduola et al, 1988;Nateghpour et al, 1993;Havlik, 1993,1994;Ritchie et al, 1996).…”
Section: Loss Of Cqr Is Associated With Previously Unidentified Pfcrtmentioning
confidence: 99%
“…This employed the intermittent drug exposure method described in (Nateghpour et al, 1993). Briefly, the parent CQ-resistant isolate K1H6/2 was exposed to AM or HF at the predetermined IC 50 concentration until the parasitemia fell to less than 40% of control values (parasite lines cultured in the absence of drug).…”
Section: Selection For Amantadine or Halofantrine Resistancementioning
confidence: 99%